Media and public agendas in electoral campaigns: Argentina, Ecuador, and Spain - Rodríguez-Díaz, Raquel (2023)
Maxwell McCombs (2004) defines electoral campaigns as “natural laboratories” for analyzing how near or far the proposals of the programs of political parties, the issues as set out by the media and the concerns expressed by the general public are from each other. This article contributes a comparative analysis in two ways. On the one hand, we systematize the existing similarities and differences in the media coverage of three general election campaigns (Ecuador 2021, Spain 2019 and Argentina 2019), based on the indicators concerning “issue agendas” and “attribute agendas” (1st and 2nd level of agenda setting). On the other hand, we explore the existing associations between the most significant issues of the media and public agendas in the framework of the three aforementioned electoral campaigns. Among the results obtained, it is worth pointing out, firstly, the dissociation of the main concerns expressed by public opinion and the most prominent issues in the main media of the three countries. In other words, the media (media agenda) give greater visibility to issues of political conflict than to issues of concerns of the citizens themselves (public agenda). Secondly, the agenda of the media studied using a content analysis of the following daily newspapers: El Comercio (Ecuador), El País (Spain) and Clarín (Argentina), is like the most unobtrusive issues (Zucker, 1978), such as corruption or political activity. They are clearly different from those issues which feature in the political and social conflicts of those countries.